A Perovskite-Based Paper Microfluidic Sensor for Haloalkane Assays - Xie, Lili; Zan, Jie; Yang, Zhijian; Wu, Qinxia; Chen, Xiaofeng; Ou, Xiangyu; Lin, Caihou; Chen, Qiushui; Yang, Huanghao (Frontiers in Chemistry, 2021)
Detection of haloalkanes is of great industrial and scientific importance because some haloalkanes are found serious biological and atmospheric issues. The development of a flexible, wearable sensing device for haloalkane assays is highly desired. Here, we develop a paper-based microfluidic sensor to achieve low-cost, high-throughput, and convenient detection of haloalkanes using perovskite nanocrystals as a nanoprobe through anion exchanging. We demonstrate that the CsPbX3 (X = Cl, Br, or I) nanocrystals are selectively and sensitively in response to haloalkanes (CH2Cl2, CH2Br2), and their concentrations can be determined as a function of photoluminescence spectral shifts of perovskite nanocrystals. In particular, an addition of nucleophilic trialkyl phosphines (TOP) or a UV-photon-induced electron transfer from CsPbX3 nanocrystals is responsible for achieving fast sensing of haloalkanes. We further fabricate a paper-based multichannel microfluidic sensor to implement fast colorimetric assays of CH2Cl2 and CH2Br2. We also demonstrate a direct experimental observation on chemical kinetics of anion exchanging in lead-halide perovskite nanocrystals using a slow solvent diffusion strategy. Our studies may offer an opportunity to develop flexible, wearable microfluidic sensors for haloalkane sensing, and advance the in-depth fundamental understanding of the physical origin of anion-exchanged nanocrystals.